2020
DOI: 10.21203/rs.3.rs-31807/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Depression in patients with knee osteoarthritis: risk factors and associations with joint symptoms

Abstract: Background To describe demographic and clinical factors associated with the prevalence and incidence of depression and explore the temporal relationship between depression and joint symptoms in patients with symptomatic knee osteoarthritis (OA). Methods 413 participants were selected from a randomized controlled trial in people with symptomatic knee OA and vitamin D deficiency (age 63.2 ± 7.0 year, 50.4% female). Depression severity and knee joint symptoms were assessed using the patient health questionnaire (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…10.3389/fnagi.2022.987732 (Zheng et al, 2021), and the long-term accumulation of these symptoms may aggravate the pain grade and joint dysfunction of patients with OA (Rathbun et al, 2018(Rathbun et al, , 2020. NIBS has been widely used in research related to depressive symptoms.…”
Section: Alleviate Symptoms Of Depressionmentioning
confidence: 99%
“…10.3389/fnagi.2022.987732 (Zheng et al, 2021), and the long-term accumulation of these symptoms may aggravate the pain grade and joint dysfunction of patients with OA (Rathbun et al, 2018(Rathbun et al, , 2020. NIBS has been widely used in research related to depressive symptoms.…”
Section: Alleviate Symptoms Of Depressionmentioning
confidence: 99%
“…Study participants were recruited from the USA, [11][12][13][14] the UK, [15][16][17][18][19] Australia, [20][21][22] the Netherlands, 23,24 Belgium, 25,26 Spain, 27,28 Canada, 29 and three Nordic countries. 30 The sample sizes in the selected studies ranged from 32 29 to 2589 15,19 participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Nine studies were single cohort studies 18,22-28,30 and 11 were multiple cohort studies. [11][12][13][14][15][16][17][19][20][21]29 All studies included in this systematic review measured subjective knee stiffness using the WOMAC.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Prolonged pain experiences can lead to negative psychological outcomes, and vice versa. A recent longitudinal study found that greater perceived OA pain and dysfunction at baseline is found to be associated with a higher incidence of depression at follow up [18]. Systematic review-level evidence has also identified that anxiety and depression symptoms in patients with OA are associated with poor healthcare outcomes, including increased doctor visits, healthcare utilisation, medication prescription, poor surgical outcomes and post-surgical pain [14].…”
Section: Introductionmentioning
confidence: 99%